Oral Everolimus for Treatment of a Giant Left Ventricular Rhabdomyoma in a Neonate—Rapid Tumor Regression Documented by Real Time 3D Echocardiography. (22nd July 2015) - Wagner, Robert; Riede, Frank Thomas; Seki, Hiroshi; Hornemann, Frauke; Syrbe, Steffen; Daehnert, Ingo; Weidenbach, Michael
Abstract : The presented case reports on successful treatment with everolimus in a neonate with left ventricular giant rhabdomyoma. The authors used a different dosage regime compared to literature and documented rapid tumor regression by 3D echocardiography. Mini‐Abstract: The authors report on rapid tumor regression of a giant rhabdomyoma with Everolimus treatment documented by three‐dimensional echocardiography.